2002
DOI: 10.1051/0004-6361:20020085
|View full text |Cite
|
Sign up to set email alerts
|

On the variability of the visual binary WR 86

Abstract: Abstract.We discuss the variability of WR 86 (WC7 (+B0 III)), a known visual binary, confirmed by Hubble Space Telescope observations (Niemela et al. 1998

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Likewise Veen & Wieringa (2000) cast serious doubt upon the photometric variability suggested for WR 50 by van Genderen et al (1991). Finally, Paardekooper et al (2002) show that the periodicity associated with WR86 is instead attributable to a β-Cephei companion.…”
Section: Possible Binary Pathwaysmentioning
confidence: 94%
“…Likewise Veen & Wieringa (2000) cast serious doubt upon the photometric variability suggested for WR 50 by van Genderen et al (1991). Finally, Paardekooper et al (2002) show that the periodicity associated with WR86 is instead attributable to a β-Cephei companion.…”
Section: Possible Binary Pathwaysmentioning
confidence: 94%
“…4, Table 2). If the frequency resolution of the observations made by Paardekooper et al (2002) is taken into account, it can be stated that the first two modes are the same as those found by Paardekooper et al (2002).…”
Section: Appendix A: Notes On Individual Starsmentioning
confidence: 74%
“…Owing to the evident variability, the star was named V1035 Sco (Kazarovets & Samus 1997). A detailed photometric and spectroscopic study was later performed by Paardekooper et al (2002). They concluded that the short-period photometric variability of V1035 Sco should be attributed to the secondary component and can be described by two modes with frequencies 6.914 and 7.236 d −1 .…”
Section: Appendix A: Notes On Individual Starsmentioning
confidence: 99%
“…Likewise Veen & Wieringa (2000) cast serious doubt upon the photometric variability suggested for WR 50 by van Genderen et al (1991). Finally, Paardekooper et al (2002) show that the periodicity associated with WR86 is instead attributable to a β-Cephei companion.…”
Section: Possible Binary Pathwaysmentioning
confidence: 94%